Membangun Pemasaran Digital Melalui Media Website Berbasis Wordpress pada Usaha Mikro Bakpia Karunia di Kecamatan Tegal Selatan - Raharjo, Gunawan; Yaqin, Ainul; Afif, Zain (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pamulang, 2025)
This PKM activity was carried out to support the marketing digitization process at Karunia MSMEs located in South Tegal District. These MSMEs previously conducted traditional marketing without utilizing sufficient digital technology. Through this program, the implementation team provided intensive assistance for 12 weeks with a focus on developing digital promotional media in the form of a WordPress-based website, as well as business visual identity design in the form of logos and banners. In addition, training on the basics of digital marketing and social media optimization was also delivered to improve the ability of business actors to manage promotions independently. The results of this activity include the creation of digital tools that can expand market reach, strengthen brand image, and increase the competitiveness of MSMEs in the digital transformation era. It is expected that the results obtained can make a sustainable contribution in supporting business growth and strengthening the presence of local products in a wider market. This program also opens up opportunities for collaboration between businesses and digital communities in the future.